2020
DOI: 10.20944/preprints202007.0403.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Complete Quantum Information in the DNA Genetic Code

Abstract: We find that the degeneracies and many peculiarities of the DNA genetic code may be described thanks to two closely related (fivefold symmetric) finite groups. The first group has signature $G=\mathbb{Z}_5 \rtimes H$ where $H=\mathbb{Z}_2 . S_4\cong 2O$ is isomorphic to the binary octahedral group $2O$ and $S_4$ is the symmetric group on four letters/bases. The second group has signature $G=\mathbb{Z}_5 \rtimes GL(2,3)$ and points out a threefold symmetry of base pairings. For those groups, the representations… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Over the last few years, the authors of this article have found that some mathematical techniques employed for quantum information processing and quantum computing may also apply to biology at the genome scale. More precisely, group theory and representations of symmetries with characters of finite groups have been used for topological quantum computing (TQC) [19] or elementary particles [29], and the the encoding of proteins [30]. Methods for dealing with infinite groups and SL(2, C) representations of such groups in TQC papers [5,31] were similarly employed for transcription factors [6] and miRNAs [6].…”
Section: Discussionmentioning
confidence: 99%
“…Over the last few years, the authors of this article have found that some mathematical techniques employed for quantum information processing and quantum computing may also apply to biology at the genome scale. More precisely, group theory and representations of symmetries with characters of finite groups have been used for topological quantum computing (TQC) [19] or elementary particles [29], and the the encoding of proteins [30]. Methods for dealing with infinite groups and SL(2, C) representations of such groups in TQC papers [5,31] were similarly employed for transcription factors [6] and miRNAs [6].…”
Section: Discussionmentioning
confidence: 99%
“…Over the last few years, the authors of this article have found that some mathematical techniques employed for quantum information processing and quantum computing may also apply to biology at the genome scale. More precisely, group theory and representations of symmetries with characters of finite groups have been used for topological quantum computing (TQC) [14] or elementary particles [38], and the encoding of proteins [39]. Methods for dealing with infinite groups and SL(2, C) representations of such groups in TQC papers [11,40] were similarly employed for transcription factors [12] and miRNAs [12].…”
Section: Discussionmentioning
confidence: 99%
“…We made use of group theory for investigating transcription factors in genetics. Finite group theory plays a big role in the attempts to model the genetic code, see [25,26] and other references therein. Finitely generated groups (whose cardinality is infinite) are necessary to deal with the secondary structures of proteins [2].…”
Section: Discussionmentioning
confidence: 99%